2018
DOI: 10.1101/431650
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Redistribution of a glucuronoxylomannan epitope towards the capsule surface coincides with Titanisation in the human fungal pathogenCryptococcus neoformans

Abstract: 43Disseminated infections with the fungal species Cryptococcus neoformans or, less 44 frequently, C. gattii, are a leading cause of mortality in immunocompromised 45 individuals. Central to the virulence of both species is an elaborate polysaccharide 46 capsule that consists predominantly of glucuronoxylomannan (GXM). Due to its 47 abundance, GXM is an ideal target for host antibodies, and several monoclonal 48 antibodies (mAbs) have previously been derived using purified GXM or whole 49 capsular preparations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Occurrences of fungal invasive diseases are always caused by invading fungi and also involved with aspects of hosts closely [1][2][3]. Studies have shown the raised body temperature, limited nutrients of glucose and metal ions, phagocytosis by phagocytes and cellular immunities are powerful weapons for fungal elimination in hosts [4][5][6][7][8][9][10], while fungal evolved strategies in return, such as temperature resistance, polysaccharide capsule and melanin production, morphology switching, and virulence gene expressions [11][12][13][14][15][16]. Nonetheless, the mechanisms of fungal central nervous system (CNS) invasion have not been determined, which is also a mystery in cryptococcosis, a life-threatening fungal invasive disease, initialized by human pathogen Cryptococcus neoformans [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Occurrences of fungal invasive diseases are always caused by invading fungi and also involved with aspects of hosts closely [1][2][3]. Studies have shown the raised body temperature, limited nutrients of glucose and metal ions, phagocytosis by phagocytes and cellular immunities are powerful weapons for fungal elimination in hosts [4][5][6][7][8][9][10], while fungal evolved strategies in return, such as temperature resistance, polysaccharide capsule and melanin production, morphology switching, and virulence gene expressions [11][12][13][14][15][16]. Nonetheless, the mechanisms of fungal central nervous system (CNS) invasion have not been determined, which is also a mystery in cryptococcosis, a life-threatening fungal invasive disease, initialized by human pathogen Cryptococcus neoformans [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%